(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
The objective of this article is to present a university extension experience with focus on analyzing the importance of vegetation in urban and developed areas. A hands-on methodology was used to achieve this this goal through extension activities from the project “Learn By Doing” (Aprender Fazendo”) for elementary and high school students from public schools and undergraduate students from Universidade Federal de Goias, Aparecida de Goiânia. The main results revealed multidisciplinary practices of teaching through field activities. Thus, from the geosciences perspective, it was considered the landscape assessment of Conservation Units and the relation between local geology and soil and spring preservation with native vegetation. From the cartographic perspective, the undergraduate students created thematic maps which were further analyzed by high school students.